The Influence of Digital Transformation, Intellectual Capital, and Stakeholder Pressure on Sustainability Report Disclosure - Devinta Cahya Ningsih; Sri Retnoningsih (Jurnal Penelitian Ekonomi dan Bisnis, 2026)
This study is motivated by the growing importance of corporate transparency and accountability for social, environmental, and economic impacts. In Indonesia, sustainability reporting, which was previously voluntary, has become increasingly essential due to stronger stakeholder demands and evolving regulations—particularly in the energy sector, which contributes significantly to environmental impacts and often faces public scrutiny. This study aims to analyze the effects of digital transformation, intellectual capital, and stakeholder pressure on sustainability report disclosure in energy sector companies listed on the Indonesia Stock Exchange (IDX) during 2021–2023. Using secondary data from sustainability and annual reports, a purposive sampling method was applied to 89 energy companies, resulting in 84 observations, analyzed through panel data regression using Eviews 10. The results show a coefficient of determination (R²) of 0.82, indicating that 82% of the variation in sustainability report disclosure is explained by the independent variables. Digital transformation, consumer pressure, and environmental pressure significantly influence sustainability report disclosure, while intellectual capital and investor pressure do not. Theoretically, this study enriches the sustainability disclosure literature by integrating digital transformation and stakeholder pressure into the analytical framework. Practically, it provides insights for policymakers and company management to strengthen digital initiatives and stakeholder responsiveness to enhance the quality of sustainability reporting.